Acute complete injuries of the lateral ligament complex of the ankle in adults: A Comparison study of results of conservative versus surgical treatment - معروف, عمار; يوسف, صفوان; سعد , معن (Latakia University Journal -Medical Sciences Series, 2022)
Objective: to evaluate the functional outcomes and the devolopment of complications after both conservative and surgical treatments of acute complete raptures of the lateral ligament complex of the ankle in adults . Patients and methods: A retrospective-prospective study included 42 adult patients between the age of 18 and 59 years old. the patients were divided into two groups (conservative and surgical). the AOFAS & FADI indexes were performed after 6 weeks, 6 months, and 1 year after treatment. the duration of the research was two years, from march 2019 to march 2021. Results: There were statistically better results in the surgically treated group according to the FADI index and the development of lateral ankle instability, with no statistical difference between the two groups according to the AOFAS index . the complications rate was higher in the first group(conservative). recurrence occurred in 11.5% and chronic Lateral instability in 19.2% of patients. gender and age did not affect the results Conclusion: : considering the high incidence and the high rate of miss-diagnosis of complete raptures of the ankle LCL, we recommend subjecting patients sustaining a lateral ankle sprain to a thorough clinical and radiographic evaluation . we also recommend surgical treatment for acute complete raptures of the lateral ligament complex of the ankle especially in young and athletic patients to reduce the incidence of lateral ankle instability, and to speed up their return to pre-injury activity levels